Constraints Faced by the Farmers in Getting Agriculture Technology Information Under ATMA in Western Region of Rajasthan - Chouhan, Nisha; Henry, Chitra; Solanki, Dilip Kumar (Indian Journal of Extension Education, 2013)
The present investigation was undertaken to know the constraints faced by farmers in getting agriculture technology  information under Agriculture Technology Management Agency (ATMA). Astudy was undertaken in Western Rajasthan.  The major constraints identified were 'Constraints in promotion of Agriculture and Allied fields', 'Marketing constraints',  'Ecological constraints', 'Socio-political constraints', and 'Technical constraints'. The results showed that 'Ground water  level going down day by day, 'Lack of proper communication about marketing facility', 'Erratic rainfall hinders the  acceptance of new varieties', ' Interferences by anti social elements in allocation of demonstration due to political reason'  ,'Lack of technology about post harvesting technology' were found to be the highest faced constraints by the respondents.  The least constraints identified under these categories were ' Short supply of electricity for irrigation', 'Low price just after  harvesting' , 'Poor performance of technologies in drought condition discourage the farmers' , 'Dominance of general caste  in getting benefits under ATMA programme' , 'Lack of technical knowledge about animal rearing' respectively. The  finding of the study indicate that it is imperative to call for attention from government, policy makers, and planners to  design effective policy/strategy that would ensure to measures overcome the constraints faced by the farmers in reaping  the benefits of ATMA.
Keywords: ATMA; constraints; information; communication